Etnotherapeutik: Intervensi Komunikasi Perawat Berbasis Silih Asah dan Silih Asih bagi Resiliensi Kanker Paru - Muthi Khairunnisa Aiman; Palito Berliano; Bilal Ali Arsy; Firdha Hanifah Suparlan; Aena Nur Safitri; Tri Nur Aini Noviar (Jurnal Komunikasi, 2026)
Lung cancer is one of the leading causes of cancer-related death in Indonesia, significantly affecting patients both physically and psychologically during chemotherapy. Resilience serves as a key psychological factor that helps patients adapt, endure stress, and maintain treatment adherence despite various challenges. This study aimed to analyze the influence of Sundanese local wisdom values—silih asih (empathy and compassion) and silih asah (mutual learning)—as an ethnotherapeutic communication model designed to strengthen resilience in lung cancer patients. A one-group pretest–posttest design was employed, involving 20 patients at RSUD Welas Asih, Bandung, who were selected through total sampling based on the inclusion criteria. Data were obtained using a modified Connor-Davidson Resilience Scale (CD-RISC) consisting of 48 Likert-scale items administered before and after the Trisilas-based therapeutic communication intervention. Data analysis employed Bayesian ordinal logistic regression to accommodate the small sample size and generate stable estimates. The results revealed that silih asih had the most substantial positive effect on patient resilience, followed by silih asah, while silih asuh was not statistically significant. Empathic communication increased resilience by up to 45%, and educational communication by approximately 40%. Thus, ethnotherapeutic communication grounded in silih asih and silih asah effectively enhances resilience, psychological well-being, and holistic nursing care. Keywords: Ethnotherapeutic communication, Silih Asih, Silih Asah, resilience, lung cancer